News on preoperative chemotherapy for breast cancer: according to the proceedings of the 33rd Annual Breast Cancer Symposium (December 8–12, 2010, San-Antonio, USA) - S. M. Portnoy (Опухоли женской репродуктивной системы)
Effective preoperative systemic therapy is a key stage of treatment for locally advanced breast cancer. The results of recent studies, presented at the symposium, give an insight into new possibilities of chemotherapy. The results that are most interesting and practically useful have been obtained when treating Her-2-positive tumors.